Factors Affecting Unmet Need of Family Planning Among Married Tharu Women of Dang District, Nepal - Chet Kant Bhusal; Sigma Bhattarai (Hindawi Limited, 2018)
Background. Increase in population plays a decisive role in providing universal access to reproductive health; however, there is very limited evidence about the reason of unmet need among marginalized and tribal communities such as Tharus. This study aimed to determine the factors affecting unmet need of family planning among married Tharu women of Dang, Nepal. Methods. Community-based cross-sectional household survey among 650 married Tharu women of age group 15-49 in October 2015 to April 2016 was conducted in Dang district, Nepal. Randomly 3 wards were selected from each Tulsipur municipality, Hekuli Village Development Committee, and Pawan Nagar VDC. Results. The mean age and parity were 30±7.31 and 2±0.69, respectively. Out of 650 women, 47% were using contraceptives. Westoff model was used for calculating total unmet need which is 49%, where unmet need for limiting and spacing was 27% and 22%, respectively. Hence after combining the current users and total unmet need, total demand for family planning was 96%. After adjustment, significant relation was observed between number of living sons ≥ 1 and unmet need of family planning (OR= 0.4; CI=0.2-0.8, p=0.01 ), similarly for women education; lower secondary level (OR=0.3; CI=0.1-0.6, p=0.01) and secondary (OR=0.1; CI=0.03-0.4, p=0.01); husband education, lower secondary level (OR=0.3; CI=0.1-0.6, p=0.01) and secondary (OR=0.4; CI= 0.2-0.9, p=0.04); and husband occupation, wage labor (OR=0.6; CI=0.4-0.99, p=0.05). In addition, having very good knowledge about method was also significantly associated (OR=0.49; CI= 0.2-0.97, p= 0.04). Conclusion. Unmet need of family planning was significantly higher among less than secondary educated women. It is also predisposed by spouse education, partner's occupation, and number of living sons. This study concerns the need for all stake holders to focus on strategic behavior communication program regarding reproductive health.